ANALYSIS OF THE FOREIGN EXPERIENCE OF THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESSES IN AGRICULTURAL COMPLEXES AND THE POSSIBILITY OF ITS APPLICATION IN SME IN THE APK OF KAZAKHSTAN - A.U. Tatikova, (Academic Journal of Physical and Chemical Sciences, 2019)
Small and medium-sized businesses play an important role in any country: it provides employment, generates healthy competition, saturates the market with new goods and services, and provides for the needs of large enterprises. Medium-sized business is a segment of entrepreneurship that has a significant impact on the development of national markets in the world, linking large businesses, small enterprises and consumers. Mediumsized businesses are characterized by such features as a high share in the economy, leadership in innovation, focus on domestic markets, flexibility and, at the same time, scale, limitation in number and revenue, and government support. Medium business is the backbone of the economy of any developed country as it creates jobs, produces new types of goods and creates the preconditions for the development of healthy competition.